Implementation of E-Book Flip PDF Professional Learning Sepak Takraw in College Students - Silvi Aryanti; Arizky Ramadhan; Novritika Novritika; Fitriana Fitriana; Samsul Azhar; Rizki Gustaman; Frayesi Frayesi (Universitas Riau, 2024)
Media is one of the determining factors for success in physical education learning. In the 5.0 era, the media provided is expected to be informative and efficient so that it can facilitate the learning process and obtain maximum learning results. This research aims to determine the use of Professional Flip PDF Based Sepak Takraw Learning E-Books among students through the application of media development carried out by the author, namely flip PDF e-book media in sepak takraw learning. This research is quantitative research on the application of the use of e-book flip pdf media. The subjects of this research were 20 students in the third semester of Physical Education and Health, Faculty of Teacher Training and Education, Universitas Sriwijaya. The stage of this research is to conduct a survey on the use of professional e-book flip pdf media among students. Data analysis used was the percentage of success in applying media to takraw learning outcomes. The research results obtained were 80.1% which were included in the feasible and efficient category based on the results carried out to help the learning and success of sepak takraw. The findings of this research are that the E-Book Flip PDF Professional research product can be used as a reference for student teaching materials in sepak takraw learning.